Democracy, Rights, Community: Examining Ethical Frameworks for Federal Public Health Emergency Response. (2nd April 2016) - Myers, Nathan
Abstract : Public health emergencies like the H1N1 pandemic and the recent response to Ebola highlight the challenge that public health officials face when balancing protection of the public with upholding constitutional and ethical principles. Analyses of the report of the Presidential Commission for the Study of Bioethical Issues and of ethics documents produced by the Ethics Subcommittee of the Centers for Disease Control and Prevention before and after H1N1 revealed the presence of, and correlations between, three ethical frameworks. The findings indicate the power of the collective voice in public health emergencies and the vital importance of democratic participation and deliberation in better preparing the United States for future emergencies.